Pendekatan Model Realistic Mathematic Education (RME) Berbantuan Video AnimasiTerhadap Peningkatan Hasil Belajar Matematika Siswa Sekolah Dasar - Anwar, Rosihan; Firman, Firman; Desyandri, Desyandri (Innovative: Journal Of Social Science Research, 2024)
Education has an important role in educating the nation's life. However, students' mathematics learning outcomes in elementary school still show low figures, especially in fractions. This research aims to explore the effect of implementing the Realistic Mathematic Education (RME) learning model assisted by animation media on the mathematics learning outcomes of class V students at SD Negeri 29 Simpang Kuayan Dua Koto District, Pasaman Regency. This research is a quantitative research with a quasi experimental design research type and the design used is a non-equivalent control group. Quasi Experimental design. Data was collected through learning outcomes tests and motivation questionnaires. The results show that the application of animation-assisted RME provides a significant improvement in student learning outcomes. This research recommends the application of the RME model to improve mathematics learning outcomes.